2021
DOI: 10.1038/s41467-021-27297-2
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore-mediated zinc acquisition enhances enterobacterial colonization of the inflamed gut

Abstract: Zinc is an essential cofactor for bacterial metabolism, and many Enterobacteriaceae express the zinc transporters ZnuABC and ZupT to acquire this metal in the host. However, the probiotic bacterium Escherichia coli Nissle 1917 (or “Nissle”) exhibits appreciable growth in zinc-limited media even when these transporters are deleted. Here, we show that Nissle utilizes the siderophore yersiniabactin as a zincophore, enabling Nissle to grow in zinc-limited media, to tolerate calprotectin-mediated zinc sequestration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…There is emerging evidence that pathogens use Zn acquisition systems during infection, through either-the elaboration of Zn-scavenging molecules, transport systems for Zn ( 8 ), or import of host-derived Zn containing molecules ( 9 11 ). It was recently shown that yersiniabactin, previously characterized as an iron siderophore, also binds Cu ( 12 , 13 ) and Zn ( 14 ) and that the yersiniabactin system is active during infections ( 12 , 14 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is emerging evidence that pathogens use Zn acquisition systems during infection, through either-the elaboration of Zn-scavenging molecules, transport systems for Zn ( 8 ), or import of host-derived Zn containing molecules ( 9 11 ). It was recently shown that yersiniabactin, previously characterized as an iron siderophore, also binds Cu ( 12 , 13 ) and Zn ( 14 ) and that the yersiniabactin system is active during infections ( 12 , 14 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, siderophores including pyridine-2,6-bis(thiocarboxylic acid) (PDTC), pyochelin, micacocidin and yersiniabactin bind Zn with high affinity 114 120 . In fact, scavenging of Zn by yersiniabactin promotes Enterobactericae colonization in the inflamed gut, illustrating the importance of siderophore-mediated Zn acquisition in host colonization 121 . In addition to Zn-binding siderophores, secreted small molecules, termed ‘zincophores’, have been identified from numerous pathogenic bacteria.…”
Section: Zn and Mn At The Infection Interfacementioning
confidence: 99%
“…First, some host cells control microbial growth through nutrient limitation. In addition to iron and zinc sequestration [56], restricted access to other metal ions such as Cu 2+ and Mn 2+ can reduce microbial fitness and growth [57]. Most intracellular bacteria are auxotrophic for purines, pyridines and amino acids, which, coupled with the known metabolic restrictions of immune cells, indicates a link between host cell metabolism and growth limitation of intracellular pathogens [58].…”
Section: Role Of Siderophores As Diagnostic Target In Various Patient...mentioning
confidence: 99%